Preventing Violent Extremism with Former Extremists in Schools: A Media Analysis of the Situation in Germany - Gansewig, Antje (Terrorism and political violence, 2023)
During recent years, the inclusion of former extremists in preventing and countering violent extremism (P/CVE) has increased internationally. This paper addresses the issue of the involvement of former extremists in school-based work to prevent violent extremism. It provides a media analysis of the content of 151 newspaper articles (published between 2001 and 2019) regarding 133 lectures given by former extremists in German schools. The analysis shows that the lectures contain mostly movement- and biography-based narration and points to some critical aspects (e.g., detailed depictions of violence, insensitive language). Furthermore, the findings indicate that some former extremists engaging in PVE might not have completed the deradicalization process. Moreover, certain former extremists could have further motives for engaging in prevention work in schools, in addition to making amends for previous actions. Among them appears the need for a compensation mechanism or a platform to advertise their activities. Therefore, we emphasize the importance of a differentiated view of former extremists’ role in PVE, especially when working with children and juveniles.